INFLUÃŠNCIA DE ALGUNS FATORES NO CRESCIMENTO, GERMINAÃ‡ÃƒO E PRODUÃ‡ÃƒO DE CONÃDIOS DE ð˜”ð˜¦ð˜µð˜¢ð˜³ð˜©ð˜ªð˜»ð˜ªð˜¶ð˜® ð˜¢ð˜¯ð˜ªð˜´ð˜°ð˜±ð˜ð˜ªð˜¢ð˜¦ (METSCH.) SOROKIN - Santos, Alda Luiza Loureiro dos; Azevedo, JoÃ£o LÃºcio de; Shirose, Issao (REVISTA DE AGRICULTURA, 2020)
INFLUÃŠNCIA DE ALGUNS FATORES NO CRESCIMENTO, GERMINAÃ‡ÃƒO E PRODUÃ‡ÃƒO DE CONÃDIOS DE ð˜”ð˜¦ð˜µð˜¢ð˜³ð˜©ð˜ªð˜»ð˜ªð˜¶ð˜® ð˜¢ð˜¯ð˜ªð˜´ð˜°ð˜±ð˜ð˜ªð˜¢ð˜¦ (METSCH.) SOROKIN